Pengaruh Penjualan, Beban Pokok Penjualan dan Biaya Operasional terhadap Laba Bersih: Studi pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2023 - Apsari, Emiliana Putri; Mulyani, Sri; Mulyani, Ulva Rizky (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
This research aims to analyze the effects of sales, cost of goods sold, and operating costs on net income in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This type of research is quantitative using secondary data in the form of annual reports. The study population was 125 companies. The sampling technique used is a purposive sampling method, resulting in a sample of 46 companies selected. The analysis technique used is descriptive statistical tests, model selection tests, panel data regression tests, and hypothesis tests. The results of this study's hypothesis testing show that sales has a positive effect on the net income, cost of goods sold has a negative effect on net income, while operating costs has a no effect on the net income.